2001
DOI: 10.1007/s001270170048
|View full text |Cite
|
Sign up to set email alerts
|

Perception of stigma among family members of individuals with schizophrenia and major affective disorders in rural Ethiopia

Abstract: Stigma was found to be a common problem, with few differences between socio-demographic groups or between types of mental disorder. Beliefs about causes differ from those held by professionals. Popular beliefs and attitudes must be taken into account when planning for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
172
7
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(204 citation statements)
references
References 12 publications
20
172
7
5
Order By: Relevance
“…These findings accord with several previous studies from high-income 21 countries (Choe et al, 2008;Hodgins et al, 2007;Silver et al, 2011). The burden of stigma, discrimination and disrespect experienced by people with SMI in rural Ethiopia has already been reported (Shibre et al, 2001). In this study, only people with SMI and none of the comparison group reported experiencing the humiliation of being mocked by children in their own community.…”
Section: Violent Victimizationsupporting
confidence: 92%
“…These findings accord with several previous studies from high-income 21 countries (Choe et al, 2008;Hodgins et al, 2007;Silver et al, 2011). The burden of stigma, discrimination and disrespect experienced by people with SMI in rural Ethiopia has already been reported (Shibre et al, 2001). In this study, only people with SMI and none of the comparison group reported experiencing the humiliation of being mocked by children in their own community.…”
Section: Violent Victimizationsupporting
confidence: 92%
“…So, reducing stress, isolation and stigmatization is very important for reducing depression among caregivers of schizophrenic patients (38,46) and must be taken into account when planning for intervention by mental health professionals (47) , better liaison is required between psychological medical professionals and caregivers to see whether they are psychologically helping caregivers of schizophrenic patients to know about their severity of depression and treat it (36) .…”
Section: Psychosocial Burden Among Caregivers Of Patients ………mentioning
confidence: 99%
“…Beliefs and attitudes about mental illnesses and patients with them are related to factors such as age, gender, marital status, education level, socioeconomic level, and contradictory results have been reported in the literature in which way these sociodemographic characteristics affect attitudes and beliefs about mental illnesses (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%